Training 21st Century Students' Critical Thinking Skills Through Social Studies Learning - Irma Dwina (Social Studies Conference Proceedings, 2022)
This article aims to describe how to train students' critical thinking skills in the 21st century through social studies learning. The 21st century is defined as a century in which so many aspects of life have changed, including the world of education. Learning methods in the 21st century focus on students or student centers. Equipping students to be able to compete in the 21st century is not enough just with knowledge, so there needs to be a balance, namely with skills. In the 21st century, thinking skills are needed to adapt to today's global life. It is important for students to help solve problems. The teacher has space to design learning in such a way that a meaningful learning process occurs. IPS material is designed to provide awareness to students as responsible citizens. The existence of social science is very relevant in preparing students who can face challenges in the 21st century. The paradigm shift in the 21st century requires social studies education to innovate. Innovations are made in social studies learning so that it can adapt to face various challenges in the 21st century. Teachers can design learning processes by applying relevant methods and models by involving students' thought processes so as to be able to train students' skills.